2012
DOI: 10.1177/230949901202000205
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Instillation following Arthroscopic Anterior Cruciate Ligament Reconstruction: A Double-Blinded, Randomised Controlled Study

Abstract: purpose. To assess the effect of hyaluronic acid instillation after arthroscopic anterior cruciate ligament (ACL) reconstruction for improving pain, range of movement, and function of the knee. Methods. 28 men and 4 women underwent arthroscopic ACL reconstruction for isolated ACL rupture (partial or complete) and instability after recreational sports injury 2 to 120 months earlier.They were randomised to undergo arthroscopic ACL reconstruction followed by intra-articular viscoseal instillation (13 men and 3 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Exogenous hyaluronic acid was reported to stimulate de novo synthesis of hyaluronic acid, and inhibit the release of arachidonic acid and interleukin-1αinduced prostaglandin E 2 synthesis, which reduced the anti-inflammatory response for pain control (35). One included RCT reported that hyaluronic acid treatment was capable of substantially alleviating pain and symptoms within 2 days after arthroscopic anterior cruciate ligament reconstruction (18). Another RCT also reported that statistically significant pain reduction was found one week postoperatively in arthroscopic surgery (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous hyaluronic acid was reported to stimulate de novo synthesis of hyaluronic acid, and inhibit the release of arachidonic acid and interleukin-1αinduced prostaglandin E 2 synthesis, which reduced the anti-inflammatory response for pain control (35). One included RCT reported that hyaluronic acid treatment was capable of substantially alleviating pain and symptoms within 2 days after arthroscopic anterior cruciate ligament reconstruction (18). Another RCT also reported that statistically significant pain reduction was found one week postoperatively in arthroscopic surgery (26).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous hyaluronic acid injected into the arthritic joint space has been shown to improve the qualitative and quantitative properties of endogenous hyaluronic acid and therefore improve joint lubrication (17). In a randomized controlled study (RCT), intra-articular hyaluronic acid was reported to improve pain control and swelling after arthroscopic anterior cruciate ligament reconstruction (18).…”
mentioning
confidence: 99%
“…Early viscosupplementation in arthroscopic partial meniscectomy was found to have conflicting results and a possible improvement in short-term pain is not showed in all level I studies [178][179][180] . Different studies on viscosupplementation after ACL reconstruction evidenced inflammation, swelling and pain reduction only in the immediate post-operative period, without any difference in the longterm 69,181,182 . Conversely, three RCTs showed significant pain and clinical scores improvement for HMW HA after knee arthroscopy in knee OA [183][184][185] .…”
Section: Ha After Knee Arthroscopymentioning
confidence: 91%
“…The following are important considerations for IAHA instillation following arthroscopic surgery:Patients with persistent knee pain following arthroscopy [26]Patients with mild knee OA who have undergone arthroscopic partial meniscectomy and debridement [27]…”
Section: Resultsmentioning
confidence: 99%
“…Patients with mild knee OA who have undergone arthroscopic partial meniscectomy and debridement [27]…”
Section: Resultsmentioning
confidence: 99%